Efficient adsorption and in situ solidification of cesium from aqueous solution using mesoporous MnO2@SBA-15. (January 2023) - Zhang, Yanming; Xiong, Yingwei; Xian, Qiang; He, Xinmiao; Dan, Hui; Ding, Yi
Graphical abstract: Highlights: Cs + was effectively adsorbed from aqueous solution by mesoporous MnO2 @SBA-15. Adsorbed Cs + was in situ solidified through sintering at low temperature. Glass ceramics with quartz and braunite mixed phases were obtained at 800 ℃. Cristobalite and braunite mixed phases were obtained at 900 and 1000 ℃. The obtained glass ceramics exhibited good compactness and aqueous stability. Abstract: MnO2 @SBA-15 adsorbents were prepared and applied for the adsorption and in situ solidification of Cs + . The adsorption and in situ solidification performance of the obtained MnO2 @SBA-15 were systematically investigated. The results demonstrated that the Cs + adsorption capacity of MnO2 @SBA-15 reached 76.63 mg/g. The adsorption data can be well fitted by the Langmuir model and Pseudo-second-order model. Moreover, Cs + was in situ solidified in glass ceramic matrix through simple sintering the MnO2 @SBA-15 adsorbed Cs + mixtures at low temperature (800–1000 ℃). The glass ceramic sintered at 800 ℃ exhibited quartz and braunite two phases. With increasing temperature to 900 and 1000 ℃, quartz transformed to cristobalite. At 900 and 1000 ℃, glass ceramics with cristobalite and braunite mixed phases were obtained. The obtained glass ceramics showed good compactness and excellent aqueous durability. Owing to its efficient adsorption and in situ solidification capacity, MnO2 @SBA-15 is a promising material for cesium removal and solidification.